A curricular framework for flourishing in education - Ergras, Oreg; Gilead, Tal; Eilam, Efrat; Kyza, Eleni A.; Akar, Bassel; Buck, Marc F.; Kumar, Smita (My University, 2022)
This chapter proposes frameworks for education in and for fourishing by moving from general concepts and ideas about fourishing articulated in the previous chapters to the level of educational implementation and practice.The frameworks proposed are not meant to be prescriptive, but rather to ofer a grounded and broad perspective that can take an informed approach in orienting education toward fourishing and refect sensitivity to the variety of social-cultural-political contexts within which education takes place worldwide. The chapter outlines premises stemming from previous chapters, situating education as a complex phenomenon. Guiding principles are developed to form the basis of two frameworks. The frst is a framework for education in and for fourishing that identifes, defnes and positions in context the components of: a) curriculum, teaching and assessment; b) learning; and c) fourishing aims and manifestations.The second is a curricular framework for education in and for fourishing based on six domains featuring six learning trajectories that expand the pillars of education introduced in the Delors Report.
Keywords: Premises stemming; Situating education; Flourishing